Cellulose acetate electrospun nanofibers for drug delivery systems: Applications and recent advances. (15th October 2018) - Khoshnevisan, Kamyar; Maleki, Hassan; Samadian, Hadi; Shahsavari, Shadab; Sarrafzadeh, Mohammad Hossein; Larijani, Bagher; Dorkoosh, Farid Abedin; Haghpanah, Vahid; Khorramizadeh, Mohammad Reza
Graphical abstract: Highlights: The new strategies of electrospinning technique to create functional CA nanofibers illustrated. The various types of therapeutic agents incorporated into electrospun CA fibers discussed. The particular characteristics of CA electrospun nanofibers loaded with therapeutic agents have defined. The advantages of CA nanofibers especially in topical/transdermal drug delivery systems (DDSs) were described. Abstract: Electrospinning process of nanofibers specially derivatives of cellulose presents high behest for developing several kinds of novel drug delivery systems (DDSs) due to their specific characteristics, the simplicity, beneficial and impressive top-down fabricating procedure. Moreover, the novel techniques of therapeutic agents for entrapment into core–shell nanofibers including single, coaxial and triaxial applied for DDSs. Recently, biodegradable polymers including derivatives of cellulose, hybrid materials, artificial and natural polymers have been remarkably considered. The acetate ester of cellulose (cellulose acetate (CA)), has been widely used due to biodegradability, chemical persistence, biocompatibility, and thermal constancy for DDSs. This article submits an overview of CA electrospinning techniques, applications, and its usage as a carrier for therapeutic agents in DDSs. Furthermore, in this study, we aimed to summarize the classification of therapeutic agents comprising antimicrobial agents incorporated CA fibers, antibacterial nanoparticles incorporated CA fibers, antioxidant agents loaded CA nanofibers, systematic and anti-inflammatory agents containing CA nanofibers. Our study has been concluded that CA electrospun nanofibers could be potentially applied as biocompatible and biodegradable for DDSs specifically in purpose-designed transdermal or wound dressing patches.